PEMAHAMAN SEKOLAH TERHADAP KEBIJAKAN TENTANG PENYELENGGARAAN KURIKULUM SETARA JENDER - Abdul Syukur Ibrahim (Universitas Muhammadiyah Surakarta, 2016)
The forming and development of educational curriculum must be fitted with the reality and requirements of the stakeholders and the students by keep referring to the national education standard and other national policies. This research aims to describe objectively about the school’s understanding towards regulations number 20 year 2003 about references in national education curriculum development and international ratifications made by Indonesian government.This research employs survey research plan with multistage area cluster to 20 elementary school students as samples. In this research, the researcherplayed as the key instrument by referring to prepared questions and interview guidance. The result showed that the teachers and the principal have not gotsome proper understanding about the baseline of gender-equal curriculum policy in Indonesian language subject. The schools need information about ways indeveloping the Indonesian language subject, wether as a tool for the application of gender-equal curriculum and ways in developing gender-equal based Indonesian language study program as a media to form a positive character and ways in putting gender-equal values in Indonesian language subject.